2005
DOI: 10.1074/jbc.m506502200
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Factor IXa in the Factor Xase Complex by Protein Z-dependent Protease Inhibitor

Abstract: Protein Z-dependent protease inhibitor (ZPI) 2 was recently identified as a serpin that potently inhibits activated blood coagulation factor X (FXa) (EC 3.4.21.6) in a manner dependent on protein Z, Ca 2ϩ , and phospholipids (1-3) and the action of which is largely ablated in the presence of FVa (3). ZPI is estimated to be present at 3.8 g/ml (53 nM) in plasma, forms non-covalent complexes with protein Z in plasma, and has an apparent mobility of 72 kDa on SDS-PAGE (3, 4). ZPI is 25-35% homologous to human ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 34 publications
1
24
1
Order By: Relevance
“…However, unlike the inhibition of factor Xa by ZPI, this inhibition was not enhanced by protein Z, lipid, and calcium ion cofactors but was accelerated ϳ2-fold by heparin (not shown), again confirming the reported behavior of plasma ZPI (7). Similar to the report of Broze and co-workers (6) but contrasting that of Heeb et al (25), we were unable to detect any inhibition of factor IXa by recombinant ZPI either in the absence or presence of protein Z, phospholipid, and calcium.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…However, unlike the inhibition of factor Xa by ZPI, this inhibition was not enhanced by protein Z, lipid, and calcium ion cofactors but was accelerated ϳ2-fold by heparin (not shown), again confirming the reported behavior of plasma ZPI (7). Similar to the report of Broze and co-workers (6) but contrasting that of Heeb et al (25), we were unable to detect any inhibition of factor IXa by recombinant ZPI either in the absence or presence of protein Z, phospholipid, and calcium.…”
Section: Resultssupporting
confidence: 57%
“…Direct comparison of recombinant and plasma ZPIs verified that the two serpin forms inhibited factor Xa with equivalent rates in the presence of cofactors. Contrasting a recent report (25), we found no evidence that ZPI could inhibit factor IXa in the absence or presence of protein Z and procoagulant membranes. Our finding that ZPI was not cleaved by factor IXa under these conditions suggests that the ZPI reactive loop sequence is not recognized by free or membrane-bound factor IXa, and therefore not likely to be a physiologic target of ZPI, consistent with the initial report of Broze and co-workers (6).…”
Section: Discussioncontrasting
confidence: 57%
“…5 A recent paper supports that the ZPI may be an unusual physiologic regulator of both the intrinsic FXase and the prothrombinase complexes. 6 The possible relevance of this system in regulating the coagulation response and in thrombosis arises from the PZ knock-out mice, which indicated that PZ appears to dampen the prothrombotic response. Moreover, the PZ-deficient mice exhibited prothrombotic tendency in combination with factor V Leiden.…”
Section: Introductionmentioning
confidence: 99%
“…PZ, depending on vitamin K, synthesized in liver, is cofactor [12] of protease inhibitors (ZPI) depending on weight 72 kD and PZ-ZPI association FXa and inhibits FXIa, decreases thrombin structure [13,14]. ZPI in plasma, is at very high levels according to PZ and it is connected to PZ with 1:1 proportion.…”
Section: Resultsmentioning
confidence: 99%